Confirmatory Analysis of an Organizational Culture Instrument for Corrections - Mei, Xiaohan (The prison journal, 2017)
Research has determined that organizational culture is related to employee turnover, job commitment, and job satisfaction. Assessment of this culture requires an instrument that befits the type of organization under examination. Using exploratory factor analysis, Stohr and her colleagues were able to demonstrate that the Organizational Culture Instrument (OCI) had a solid reliability and validity profile. The current study reanalyzes these data, using confirmatory factor analysis and structural equation modeling. The findings indicate that there is statistical evidence to claim validation of the OCI and its seven theoretically based dimensions.